Maximal and Explosive Muscle Strength During Hip Adduction Squeeze and Hip Abduction Press Test Using A Handheld Dynamometer: An Intra- and Inter-tester Reliability Study - Lasse Ishøi; Kristian Thorborg; Laura Krohn; Lars Louis Andersen; Asger Møller Nielsen; MIkkel Bek Clausen (International Journal of Sports Physical Therapy)
# Background